The Effect of Callisthenic Exercises on Pain Threshold, Pain Severity and Muscle Strength on Sedentary Women Diagnosed with Upper Extremity and Low Back Pain - Akyol, Betül; Arslan, Cengiz; Çolak, Cemil (My University, 2016)
Aim: This study on sedentary women diagnosed with upper extremity and low back pain isconducted to analyze the effects of calisthenic exercises on pain threshold, pain severity, andmuscle strength.Materials and Methods: Our study included 80 sedentary women, aged between 40-60, whowere diagnosed with upper extremity and low back pain; these patients were admitted to theoutpatient physical therapy clinic of a private hospital in Malatya. Patients were randomlyassigned to two groups. 40 patients underwent conservative therapy (US, HP, tens) as the controlgroup and 40 patients received conservative therapy and calisthenic exercises as the traininggroup. Both groups were administered a pre-test and post-test model. Pain threshold, painseverity, muscle strength of the subjects were assessed before and after the treatment. The datawere evaluated using IBM SPSS Statistics 22.0 package software, and the level of significance wastaken as p<0.05.Results: Based on the results of this study, patients who were treated with conservative treatmenttogether with calisthenic exercises had significantly increased muscle strength, pain thresholdvalues (p <0.05) while they also showed significantly decreased pain intensity values (p <0.05). Itwas observed that all muscle strength variables were significantly improved compared to thebaseline values after treatment with calisthenic exercise added to conservative treatment. Therewere significant differences found in muscle strength and pain threshold values between the twogroups (p<0.05).Conclusion: In conclusion, we believe that conservative treatment administered with calisthenicexercises increases muscle strength and muscle pain threshold values.
Keywords: Genel ve Dahili Tıp; Rehabilitasyon; Spor Bilimleri